2021
DOI: 10.1177/0890117121992295
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Basic Needs for Higher Education: It’s More Than Minimal Food and Housing According to California University Students

Abstract: Purpose: A student-specific definition of basic needs for higher education is warranted to inform programs and policies for underserved students. The purpose of this study was to: 1) explore how students define basic needs, 2) understand experiences of housing insecurity, and 3) understand experiences of food insecurity within the context of housing insecurity. Design: Qualitative research elicited student perceptions of basic needs and experiences of housing and food insecurity. Setting: Focus group discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…A spotlight on these factors provides implications for promoting equitable campus food access that reaches out to and empowers students to utilize resources. While the issue of student basic needs has become a priority, especially in California due to current legislative efforts, these results indicate more can be done (Laska et al, 2021;Martinez et al, 2021;UC Global Food Initiative, 2017). The addition of campus food pantries has been shown to be successful in providing crucial immediate access to food as well as bringing student experience of food insecurity to the forefront (Esaryk et al, 2021;Gammon et al, 2021;, but further research is needed to explore how students use food resources and to understand their experiences in traversing the campus food access landscape.…”
Section: Discussionmentioning
confidence: 99%
“…A spotlight on these factors provides implications for promoting equitable campus food access that reaches out to and empowers students to utilize resources. While the issue of student basic needs has become a priority, especially in California due to current legislative efforts, these results indicate more can be done (Laska et al, 2021;Martinez et al, 2021;UC Global Food Initiative, 2017). The addition of campus food pantries has been shown to be successful in providing crucial immediate access to food as well as bringing student experience of food insecurity to the forefront (Esaryk et al, 2021;Gammon et al, 2021;, but further research is needed to explore how students use food resources and to understand their experiences in traversing the campus food access landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing basic needs insecurity as a continuous variable with multiple components provides insight into severity of insecurities, rather than the traditional binary approach (food secure vs food insecure and housing secure vs housing insecure). We recommend developing and fully validating a comprehensive basic needs insecurity scale, including variables previously identified by students such as food, housing, mental health, sleep hygiene, and transportation [ 22 ]. Access to healthcare and other social risk factors may also be important components of a comprehensive basic needs insecurity scale [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the need to expand basic needs research beyond food insecurity among college students has been recognized [ 11 , 21 ]. A small qualitative study of college students in California found students define basic needs as including food, housing, mental health, sleep hygiene, and transportation [ 22 ]. Relationships between housing security and health are not as well established, perhaps due to the lack of uniformity in defining housing insecurity, and the difficulty in finding solutions to improve housing insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Although many factors may contribute to each student’s academic success, current observations of college campuses point to an increased focus on improving basic needs access as a way to support student success [ 24 , 25 ]. At the University of California (UC), the definition of “basic needs” includes “equitable access to nutritious and sufficient food; safe, secure, and adequate housing […]; healthcare […]; affordable transportation; resources for personal hygiene care; and emergency needs for students with dependents [ 26 ]”.…”
Section: Introductionmentioning
confidence: 99%